An Empirical Study of Credit Risk Determinants in UK Banks - ZHOU, YUBING (2022)
This paper explores the factors that affect banks' credit risk and looks at UK banks. The ratio of non-performing loans to gross loans is used to quantify credit risk as the dependent variable. Seven independent variables were selected, of which bank capital, size and profitability were used as bank-level independent variables, and exchange rate, GDP growth, inflation rate and unemployment were used as macroeconomic-level independent variables. In this study, 119 banks in the UK were selected as samples, spanning the period 2016 to 2020. Regression analysis was conducted using panel data and concluded that bank capital, size and exchange rate are positively and statistically significantly related to credit risk. Yield rate, GDP growth and unemployment are significantly negatively related to credit risk. In addition, the coefficient of the inflation rate is not significant.